Recurrent network as a tool for calibration in automated systems and interactive simulators - Trunov, Alexander; Malcheniuk, Alexander (Eastern-European Journal of Enterprise Technologies, 2018)
We have constructed a method for the auto-calibration and correction of values of the vector of magnetic induction, which is suitable for use under conditions of limited computational resources in microcontrollers and SoC System-on-a-Chip. The efficiency of the system in general was investigated experimentally by using an additional board, which holds six pairwise connected primary Hall sensors. Correctness of work of the algorithm was checked at the designed and fabricated microprocessor test module, the prototype of which was the most simplified variant of the popular microcontroller board Arduino. We have implemented the structure of a recurrent network that is built based on vectors-indicators and recurrent decomposition; and examined the efficiency of algorithms for the calibration and processing of peripheral information. The microprocessor module was designed and manufactured, using which we studied dependence of the magnitude of measurement error on the properties of the sensor and hardware features for the automated systems and interactive simulators. A principle of the modular structure of software was employed, which increases the percentage of reuse of software parts by the organization of requests, as well as makes it possible to create new functions without making significant changes to the existing code. To ensure the independence of software from the hardware platform of sensor realization and the system of data processing and transfer, it is equipped with a module that adapts the level of hardware abstraction. The result of its implementation is the simplified procedure for software deployment in other hardware means. All platform-dependent system functions are implemented at this level. Independence from the hardware features of platforms is provided by engaging the computational tools, techniques, tools and modules of SPI, UART interfaces, and Modbus-RTU protocol. They help configure and exchange data with peripheral devices for its further processing by a personal computer.